Multicomponent Chirp-like Jammer Excision in DSSS Communication Systems Using Hilbert-Huang Hough Transform - Yuan Ye; Mei Wenbo (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
A novel and efficient approach for multicomponent chirp-like jammer excision in direct sequence spread spectrum (DSSS) communication systems using Hilbert-Huang Hough (HH-H) transform is proposed, which is the generalization of marginal Hilbert spectrum. The approach iteratively decomposes the received signal into intrinsic mode functions (IMFs) and applies Hilbert transform to each IMF to yield Hilbert spectrum (HS), by which the embedded jammers can be well concentrated in the time-frequency plane along their instantaneous frequency laws. By performing Hough transform over the HS and searching peaks in the parameter space, parameters estimation and components reconstruction of the multicomponent chirp-like jammer are implememted. Simulation results are presented showing performance comparison between the proposed method and the fractional Fourier transform (FrFT) based method in the case of two chirp-like jammer components. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2372